ANALISIS PENYIMPANGAN (ANALISIS VARIANCE) BIAYA PROYEK PEMBANGUNAN APARTEMEN PAKERISAN DI DENPASAR (SUATU STUDI KASUS) - Sukada Wenten, I Made; Yansen, I Wayan; Astawa Diputra, I Gde (Jurnal Ilmiah Teknik Sipil; Vol. 11, No. 2 Juli 2007, 2012)
In construction businesses, it is important to understand the differences between standard costs and the actual costs. Comparing or to find the differences between actual and standard cost in the term of accounting is known as variance analysis. Real cost is the cost of material and labour that actually paid by the company. Standard cost is the cost that calculated based on the quantity of work items multiplied by coefficient of BOW and furthes analysis multiplied again by standard price from city government of public labour 2004. The material price variance is calculated is caused by comparing real material price with the standard ones. The difference happened because by the reality that the company bought material higher or lower price than the standard material price. The total bought of material price variance can be calculated by multiplying (unit) item per item material price variance with the actual quantity. Material quantity or use variance is the differences that happened because the company uses the material more or less quantity than standard quantity in the production process. The total amount of material quantity or use variance can be calculated by multiplying the material quantity variance with the standard material price per item. The calculation of variance from material price revenled that 0.38%, material quantity variance 19.04% and the total amount of material price variance is 18.60% in relation to standard material cost. Labour cost variance is about 62.01% againsts standard labour cost. The total variance of cost and labour price is 36.03% againsts standard cost and labour price. If the calculation considered the indirect cost, the total variance will be 18.90%. Also if taxes is added in the calculation the total variance will be 13.82% of the standard cost.
Keywords: Variance, penyimpangan, biaya standar, biaya sebenarnya, biaya aktual